Short-Term Stability of Hematologic Parameters in Frozen Whole Blood. (19th November 2019) - Tang, Olive; Selvin, Elizabeth; Arends, Valerie; Saenger, Amy
Abstract: Background: Complete blood counts (CBCs) are commonly obtained in large multicenter studies. We assessed the stability of 10 parameters after short-term (up to 30 days) frozen storage. Methods: We compared CBC measurements from fresh samples (n = 53) with samples stored for up to 30 days at −70 °C. We calculated the CVs and intraclass correlation coefficients. Results: Mean values of most parameters, with the exception of hemoglobin and platelet count, were significantly different by 15 days of storage. White blood cell count (CV, 38.3%; 95% CI, 31.3%–46.2%) and red cell distribution width (CV, 37.7%; 95% CI, 34.1%–41.3%) were the most variable. After 30 days, only hemoglobin remained stable and reliable (CV, 0.8%; 95% CI, 0.4%–1.3%). Conclusions: Hemoglobin remained stable in frozen blood samples stored for up to 30 days at −70 °C and may be reliably used in research studies using short-term frozen specimens. Other CBC parameters measured in stored blood are not sufficiently reliable for research or patient care.